If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 23x + -32 = 20x + -23 Reorder the terms: -32 + 23x = 20x + -23 Reorder the terms: -32 + 23x = -23 + 20x Solving -32 + 23x = -23 + 20x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-20x' to each side of the equation. -32 + 23x + -20x = -23 + 20x + -20x Combine like terms: 23x + -20x = 3x -32 + 3x = -23 + 20x + -20x Combine like terms: 20x + -20x = 0 -32 + 3x = -23 + 0 -32 + 3x = -23 Add '32' to each side of the equation. -32 + 32 + 3x = -23 + 32 Combine like terms: -32 + 32 = 0 0 + 3x = -23 + 32 3x = -23 + 32 Combine like terms: -23 + 32 = 9 3x = 9 Divide each side by '3'. x = 3 Simplifying x = 3
| p/7-3=4 | | 3x^6= | | 9y-30=150 | | t/2-14=36 | | 4u+9=37 | | x/8-1=7 | | -16x-20=13x+7 | | x/12+6=10 | | 4x+0.5y+0.25y=z | | 86-10=x | | m/6+13=19 | | h/6+8=11 | | a/9+7=16 | | w/8+4=8 | | 4x+0.5y+0.25z=1 | | 4x+0.5y+0.25y=1 | | n/9-6=0 | | e/4+14=16 | | u/3+9=18 | | 2(t-3)-3(2t-3)=3-5(3t+1) | | (1/5)(5y+10)-8=(-1/7)(21y-42) | | 8x-3-4x=x+3+x | | (5/6)y-(1/6)=(7/3) | | x-25x/100=7717.95 | | 2-5(z-1)=3z+1 | | 2x-3/3-6x+2/2=7x-1/4 | | 2(x-3)-(x-4)=-3(x+2)+2(4x-6) | | 3/4x-2/3=5/2x-7/6 | | 5x-8-2x=62+10 | | 8/10x | | x-25x/100=8227.24 | | 8227.24*7.50/100=617.05 |